Efficacy of magnetic capture in comparison with conventional DNA isolation in a survey of Toxoplasma gondii in wild house mice - Juránková, Jana; Hůrková-Hofmannová, Lada; Volf, Jiří; Baláž, Vojtech; Piálek, Jaroslav (European journal of protistology, 2014)
Toxoplasma gondii is a zoonotic parasite with a world-wide distribution. House mice (Mus musculus) play an important role as a reservoir host in the parasite life cycle. However, their detection in mouse brain is limited because the host potentially harbours only a few tissue cysts. In order to improve the diagnosis, we tested a novel protocol for T. gondii detection in mice and compared this technique to a standard PCR-based protocol using a commercial kit for DNA isolation. Efficacy of magnetic capture for isolation of T. gondii DNA from whole host brains was tested in brain samples of laboratory mice spiked with 1 up to 10(4) tachyzoites. Real-time PCR revealed that even 1-5 tachyzoites can be detected after magnetic capture. Also this method is suitable to quantify parasite numbers in mouse brains with more than 10 tachyzoite equivalents. To assess the two techniques in wild mice, we employed a dataset consisting of 243 individuals. The prevalence of T. gondii detected by magnetic capture and qPCR and by commercial isolation and PCR was 1.2% and 0%, respectively. The magnetic capture and quantitative PCR seems to be a highly sensitive and specific diagnostic method for both laboratory research and wild population surveys.
Keywords: Limit of Detection; limita detekce; Toxoplasma gondii; Quantitative PCR; Female; protozoální DNA; genetické techniky; DNA, Protozoan; magnetické jevy; zvířata; myši; Mice; Magnetic capture; ženské pohlaví; Toxoplasma; polymerázová řetězová reakce; toxoplazmóza zvířat; Polymerase Chain Reaction; Animals; Magnetic Phenomena; Toxoplasmosis, Animal; Genetic Techniques; House mice